Genome of Ganoderma Species Provides Insights Into the Evolution, Conifers Substrate Utilization, and Terpene Synthesis for Ganoderma tsugae - Jiang, Nan; Hu, Shuang; Peng, Bing; Li, Zhenhao; Yuan, Xiaohui; Xiao, Shijun; Fu, Yongping (Frontiers in Microbiology, 2021)
Ganoderma tsugae is an endemic medicinal mushroom in Northeast China, providing important source of pharmaceutical product. Comparing to other Ganoderma species, wild G. tsugae can utilize coniferous wood. However, functional genes related to medicinal component synthesis and the genetic mechanism of conifers substrate utilization is still obscure. Here, we assembled the first high-quality G. tsugae genome with 18 contigs and 98.5% BUSCO genes and performed the comparative genomics of G. tsugae genome with other Ganoderma species. G. tsugae diverged from their common ancestor of G. lingzhi and G. sinense about 21 million years ago. Genes in G. tsugae specific and expanded gene families, such as salh, phea, cyp53a1 and cyp102a, and positively selected gene, such as glpk and amie, were functionally enriched in plant-pathogen interaction, benzoate degradation and fanconi anemia pathway. Those functional genes might contribute to conifers substrate utilization of G. tsugae. Meanwhile, gene families in the terpene synthesis were identified and genome-wide SNP variants were detected in population. Finally, the study provided valuable genomic resources and offered useful hints for the functional gene mapping and investigation of key gene contributing to conifers cultivation substrate utilization and medicinal component bio-synthesis.